1991
DOI: 10.1128/iai.59.11.4089-4096.1991
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in host resistance to Mycobacterium marinum infection in mice

Abstract: Sex differences were observed in host resistance to Mycobacterium marinum infection in mice. Males were found to be more susceptible than females in terms of mortality, incidence of gross skin lesions, and bacterial load in the lungs and spleen. The degree of sex differences varied from strain to strain of test mice, in the order C3H1/I1e, A/J, and BALB/c > DBA/2, B10.A, and C57BL/6, on the basis of survival time and multiplication of organisms in the visceral organs. Although this ordering corresponded to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…Group V includes genes important toward producing reactive oxygen species (ROS) and oxidative stress, but also mediators active during bacterial infection. cell-mediated immune responses vs. female mice (Yamamoto et al, 1991). Castrating male mice before infection showed similar rates of infectivity to females and female mice given testosterone were found to be more susceptible to M. marinum compared to controls females (Yamamoto et al, 1991).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Group V includes genes important toward producing reactive oxygen species (ROS) and oxidative stress, but also mediators active during bacterial infection. cell-mediated immune responses vs. female mice (Yamamoto et al, 1991). Castrating male mice before infection showed similar rates of infectivity to females and female mice given testosterone were found to be more susceptible to M. marinum compared to controls females (Yamamoto et al, 1991).…”
Section: Resultsmentioning
confidence: 92%
“…cell-mediated immune responses vs. female mice (Yamamoto et al, 1991). Castrating male mice before infection showed similar rates of infectivity to females and female mice given testosterone were found to be more susceptible to M. marinum compared to controls females (Yamamoto et al, 1991). Although, these studies and our observations may be attributed to murine strain specificity, consistent observation of these trends distinct to each sex, combined with sex-specific microbial population densities, and across multiple modelssuggests that sex factors into immune response and to foreign microorganisms (Aziz, 2002;Marriott, 2006;Arnold, 2009;Gomez et al, 2012;Markle et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…There have been some reports about the relation between sex and mycobacterial infections using experimental murine infection, such as those due to M. intracellulare [27], M. marinum [28] and M. leprae [29]. They all showed that females were more resistant to the infections than males.…”
Section: Discussionmentioning
confidence: 99%
“…18 The few studies of sex differences in murine models of infectious respiratory disease generally investigate bacterial or mycobacterial (not viral) infection with results that vary depending on the pathogen; female C57BL ⁄ 6 mice are more susceptible to and show greater inflammatory responses to Pseudomonas aeruginosa infection than males, 3 yet male mice of various strains develop more severe lung lesions and greater mortality resulting from mycobacterial infection. 19,20 Thus, previous studies suggest that males may be more susceptible to infection because of their reduced ability to mount an appropriate inflammatory response compared with females. This lessened response may reduce cytokine-⁄ chemokine-related damage to the airways ⁄ parenchyma in males, which may be reflected in lessened responsiveness to bronchoconstrictive agents.…”
Section: Original Articlementioning
confidence: 99%